The concept of gender equality and equity: an Islamic view - Mohamed Sulthan Ismiya Begum,; Indriaty Ismail,; Zul’ Azmi Yaakob, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Equality, equity and justice are the most frequently discussed concepts that have received much attention in modern times. However, equality is emphasised regardless of gender differences, and it remains a theory. Meanwhile, equity is a practical way to achieve equality that considers human nature. In this sense, justice is the closest term to equity. Although it is used in legal areas, all Islamic doctrines are built upon justice. Hence, justice is a more general concept. These concepts have not been clearly defined, and some people view them as one. Therefore, this study conducts qualitative-based research to illuminate the differences between these terms. This undertaking attempts to indicate the connection between the concepts of justice from an Islamic point of view. Data were collected from primary and secondary sources. The Quran is used as a primary source, and written materials, including journal articles, books and web articles, are used as secondary sources. Findings show that gender equality, equity and justice are different concepts. Nevertheless, the objective of equality and equity is to promote justice among the people. The study also finds that gender equality is not acceptable in all matters. Islam considers gender equity more important than equality because it is more closely related to the doctrine of justice.